Placebo- Controlled Trial of Pharmaceutical Optimized Captopril 60mg (F-9) in Patients with Essential Hypertension for Efficacy & Biochemical Evaluation (Medical Forum Monthly, 2024)
Objective: The aim of study , to evaluate the efficacy of optimized Captopril 60 mg (F-9) with compare to placebo control for eight weeks and also analyze basic metabolism parameter such as Total Cholesterol, LDL-Cholesterol, HDL- Cholesterol, Triglycerides and Fasting blood glucose for test and control patientsStudy Design: Double-blind, randomized placebo-controlled trialPlace and Duration of Study: This study was conducted at the Department of Biochemistry, University of Karachi from September 2011 to January 2012.Materials and Methods: Patients were selected from different area of orange town and surrounding area , such as pirabad, mangopir, Pathan colony, impear colony, mastanchali , Metrovell and site area. Total eighty (80)patients were analyzed for Total Cholesterol (mg/dl) , HDL-Cholesterol mg/dl), LDL-Cholesterol mg/dl) , Triglycerides (mg\dl) and for fasting glucose level . The analysis was performed by Micro Labe 300 and kits were used of Merck. Other biochemical parameters( Liver function test, Urea, Complete blood counting, uric acid , electrolytes and protein profile) were used for safety purpose. All the parameter were studied at initial phase for test and control and after completion of trial such as eight weeks (8 weeks), parameters were studied again for test and control. Primary blood pressure such as Systolic BP - 24 hours (mmHg) and Diastolic BP - 24 hours (mmHg) was analyzed by manual method patients. After eight weeks (8weeks) trial, blood pressure was determined by same manual method for test and placebo control patients.Results: Initial result systolic blood for test patient was 149.9 + 11.2 mmHg and for placebo control was 149.2+ 10.5 mmHg. After eight week trial of optimizedCaptopril 60mg (F-9), systolic blood was reduced (140.1 ± 11.4 mmHg) as compared to placebo control such as (148.9 ± 11.3 mmHg). Like systolic blood pressure, initial diastolic blood pressure for test patient was (97.7 + 7.2 mmHg) and for placebo was (95.3+ 7.7mmHg) but after eight week trial of optimizedCaptopril 60mg (F-9), diastolic blood pressure was reduced in test patients (86.6 ± 5.4 mmHg) as compared to placebo control such as (93.9 ± 7.9 mmHg). Conclusion: The optimized Captopril 60mg (F-9)it is an excellent option for the treatment of hypertension withhigh antihypertensive efficacy, good tolerability and no biochemical effects. . It is due to low dose drug and also no effect of excipient of formulation of F-9.